PERBANDINGAN TERAPI MUSIK KLASIK DAN SENAM OTAK (BRAIN GYM) TERHADAP PENURUNAN TINGKAT STRES LANSIA DI PANTI SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH PEKANBARU - Judika Yessi Sara; Fathra Annis Nauli; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Stress is a mental problem that most suffered by elderly. Things that make elderly stressed are affected  by retire, loss of purpose in life, loss of a friend or spouse, the risk of disease, isolated from the environment, and loneliness. Nonpharmacological therapies can be applied to the stress are the classical music therapy and brain gym. The aim of this research was to identify the comparison of classic Music therapy and brain gym towards the reduction phase of Stress in the elderly. This research used quasy experimental design with pre test and post test design by comparing two treatments. This research was conducted with 34 samples, which divided into17 as classical music therapy group and  17 as  brain gym group and choosen by purposive sampling and random sampling technique. The level stress was measured with DASS (Depression Anxiety Stress Scale). The analysis used univariate by using frequencies and bivariate by using dependent t test and independent t test. The results of this research showed that significant reduction phase  stress, with p (0.036) < α(0.05). Mean score DASS of music therapy showed the reduction about 2 point, while the difference of mean pre test and post test of brain gym group was about 3.71 point. The conclusion is brain gym more effect on reduction phase stress on elderly and recommended to be applied for nursing as one intervention to help reduction phase of stress.   Keywords: brain gym, classical music therapy, elderly, the level stress